Fufang E’jiao Jiang’s effect on immunity, hematopoiesis, and angiogenesis via a systematic “compound-effect-target” analysis - Xiang Li; Xiao Xu; Ying Dong; Shusheng Fan; Xueyang Ren; Yuan Zheng; Jiamu Ma; Feng Zhang; Qingyue Deng; Xianxian Li; Yingyu He; Mengyu Sun; et al. (Food Science and Human Wellness)
Fufang E’jiao Jiang (FEJ) as a healthy food consisting of medicine food homology materials approved by China’s Ministry of Health has been extensively applied to replenish qi and nourish blood, and it has a positive impact on women’s health. To find out the material basis and mechanism of FEJ, a systematic “compound-effect-target” analysis including chemical composition resolution, zebrafish, network pharmacology, molecular docking, transcriptome, and bibliometric analysis was adopted. 124 chemical components including ginsenosides, and phenylethanoid glycosides in FEJ were discovered, and effects of FEJ on promoting the generation of immune cells, erythropoiesis and angiogenesis in zebrafish were exhibited. Based on network pharmacology, molecular docking and in vivo activity assay, 6 compounds including jionoside A1, isoacteoside, echinacoside, acteoside, lobetyolin, and rehmannioside D were identified as active components of FEJ. Transcriptome data showed that several pathways such as complement and coagulation cascades, ECM-receptor interaction, and PI3K-Akt signaling pathway were associated with proangiogenic effect of FEJ. 19 common targets were obtained through combined analysis of network pharmacology and transcriptomics, and 5 targets of them were verified by PCR. The bibliometric analysis of these common targets revealed that FEJ was related to energy metabolism, pathway in cancer, etc., which was consistent with the results of network pharmacology and transcriptome. The studies suggested that FEJ could replenish qi and nourish blood through multi-compound and multi-targets.